PENDEKATAN ERGONOMI MAKRO SEBAGAI SOLUSI PERENCANAAN SISTEM KERJA BERGILIR UNTUK MENINGKATKAN PRODUKTIVITAS, KUALITAS DAN KESELAMATAN KERJA INDUSTRI - Lamto Widodo; Bambang Pramudya; Sam Herodian; M. Faiz Syu'aib (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT According to IEA 9International Ergonomics Association), ergonomics or human factors is the scientific discipline concerned with the understanding or interactions among humans and other elements of a system, and the profession that applies theory, principles, data and methods to design in order to optimize human well-being and overall system performance. To achieve effectiveness and productivity, work system designer have to consider not only the technological aspects, but also the relationship between user and system. User satisfaction, comfortabillity, adjustablillity and worker safety, for example, are the most important parameters to be considered in the design processea. There are two ergonomics approach in the job design, i.e., micro ergonomics and macro ergonomics. Micro ergonomics analyzes task-sub task, optimize worker, focused on detail design, and generally physical measure such as length, force, lumens, decibels, time, etc. Macro ergonomics analyzezz group of worker, focused on broad overview and generally organizational and/or subjective measures such as number of people, span of controls, attiudes, morals, shift schedules and sosio-technical design. Shift work is well recognized risk factors for occuptional safety and health. Evaluation and design of working time arrangements gain importance due to economical changes and overall reduction of safety and health problems. The aim of this paper is to review the main factors of ergonomics approach applied on shift work design to improve systems productivity and occupation safety and health. Keyword: macro ergonomics, shift work design, productivity, occupation safety and health